Our boss is a good boss! : Cross-level effects of transformational leadership on work engagement in service jobs - Martínez, Isabel M. (Colegio Oficial de Psicólogos de Madrid, 2020)
In service work, emotional demands are important due to their effects on social interactions with customers, patients, pupils, etc. The purpose of this study is to examine how emotional demands and leadership are related to engagement of the team members. The sample consists of 1,079 employees nested in 124 work teams from four Spanish public organizations. Multilevel analyses showed: 1) a positive effect of emotional demands on work engagement, 2) a cross- level effect of leadership on work engagement, and 3) a cross-level moderation effect of leadership on the relationship between emotional demands and work engagement. Results suggest that shared perceptions of leadership by teams affect their work engagement levels directly and through an interaction effect on the emotional demands-engagement relationship. When employees feel emotionally overloaded, their leaders can relieve this negative impact on their levels of work engagement. Practical and theoretical implications are presented.